2009
DOI: 10.1267/ahc.09017
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Satellite Glial Cells in Rat Trigeminal Ganglion after Upper Molar Extraction

Abstract: The neurons in the trigeminal ganglion (TG) are surrounded by satellite glial cells (SGCs), which passively support the function of the neurons, but little is known about the interactions between SGCs and TG neurons after peripheral nerve injury. To examine the effect of nerve injury on SGCs, we investigated the activation of SGCs after neuronal damage due to the extraction of the upper molars in rats. Three, 7, and 10 days after extraction, animals were fixed and the TG was removed. Cryosections of the gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…We also found no evidence of SGC stress as indicated by ATF3 immunoreactivity, a member of the ATF/cAMP family of transcription factors that is upregulated by nerve injury and other stress responses (Tsujino et al, 2000). This corresponds with other studies that have not reported ATF3 in SGCs after tooth extraction (Gunjigake et al, 2009) or CCI of the ION in mice (Xu et al, 2008). However, ATF3 has been reported in SGCs 7 days following paclitaxel induced nerve injury (Peters et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found no evidence of SGC stress as indicated by ATF3 immunoreactivity, a member of the ATF/cAMP family of transcription factors that is upregulated by nerve injury and other stress responses (Tsujino et al, 2000). This corresponds with other studies that have not reported ATF3 in SGCs after tooth extraction (Gunjigake et al, 2009) or CCI of the ION in mice (Xu et al, 2008). However, ATF3 has been reported in SGCs 7 days following paclitaxel induced nerve injury (Peters et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…4A1). The time of GFAP expression in SGCs seems to vary depending on the injury model (Gunjigake et al, 2009; Mika et al, 2010; Peters et al, 2007; Xie et al, 2009). As previously reported, GFAP immunoreactivity was not seen in contralateral (control) ganglia but was visible in the trigeminal ganglia ipsilateral to the injured nerve.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond evidence of altered neuron/SGC communication in response to reduced neuronal p75NTR expression, the SGC/SGC communication axis is also likely altered by the increased incidence of gap junction Cx43 expression in SGCs, normally observed at lower levels in the absence of nerve injury . This implies increased SGC coupling may occur and also parallels changes observed following nerve injury (Gunjigake et al, 2009).…”
Section: Induction Of a Reactive State In Perineuronal Sgcsmentioning
confidence: 55%
“…Like other glial cells, the satellite glial cells are known to respond to nerve injury by up-regulating GFAP [61]. We identified Schwann cells in rhesus DRG tissue explants by the expression of p75NTR and CNPase [29,30,62].…”
Section: Discussionmentioning
confidence: 99%